Upaya Meningkatkan Produktivitas Tanaman Kakao Dengan Sistem Poliklon Di Desa Rempek Darusalam Kecamatan Gangga Kabupaten Lombok Utara NTB - Ngawit, I Ketut; Wangiyana, Wayan; Farida, Nihla; Ernawati, Ni Made Laksmi (Jurnal Gema Ngabdi, 2025)
The causes of the low productivity of cocoa plants in the village of Rempek are that the plantations are planted with inferior seeds, the sanitary conditions of the plantations are poor, they receive little care, and the plants are old. Solutions to address these problems include: intensive care of the plantations, frequent, light, and simple pruning of the plants, integrated pest management, application of organic fertilizers, and rejuvenation of the plants through a polyclonal system. Another problem that needs to be addressed is the lack of knowledge and skills of farmers in managing cocoa plantations in the polyculture system. Furthermore, the entrepreneurial skills and agricultural knowledge of the farmers are also inadequate. Due to these issues, a training and support program has been established aimed at improving the knowledge and skills of farmers in managing cocoa plants in the polyclonal system. The execution of the training activities proceeded orderly, safely, and smoothly. The knowledge and skills of the participants in cultivating cocoa plants improved, as evidenced by the participation rate and the initially low enthusiasm, which could be raised to a high level after participating in the training. The management of cocoa plantations with a polyclone system and the intensive application of agronomic practices leads to a significantly higher total number of cocoa fruits per tree and a higher total weight of dry cocoa per tree compared to cocoa plantations that are only sporadically maintained and those that are not maintained as well as monoclonals.